Deliberation and Implementation in Collaborative Governance: Insights Geopark Development in Indonesia - Dwipati, Ummul; Ibrahim, Muh Akmal; Abdullah, Muh Tang (Journal of Law Science, 2025)
Collaborative governance has emerged as a promising approach for managing sustainable tourism development in geoparks. This study examines the collaborative governance process in the development of Maros-Pangkep Geopark in South Sulawesi, Indonesia, focusing on the deliberation and implementation stages. Through qualitative analysis, the study identifies strategies for enhancing the effectiveness of these critical stages. In the deliberation stage, establishing clear protocols for inclusive dialogue, integrating scenario planning, forming thematic working groups, and instituting regular monitoring and evaluation are found to be essential for developing a robust geopark management framework. The implementation stage requires effective coordination and communication mechanisms, alignment with UNESCO Global Geopark guidelines and Sustainable Development Goals, mobilization of stakeholder resources, local capacity building, and robust monitoring and evaluation systems. The study highlights the potential of collaborative governance to deliver sustainable development outcomes, as evidenced by Maros-Pangkep Geopark's contributions to multiple SDGs. However, sustaining and scaling up these achievements demands ongoing commitment, adaptability, and collaboration among stakeholders. The findings offer valuable insights for enhancing collaborative governance in geopark management, emphasizing stakeholder engagement, strategic planning, and adaptive management. The Maros-Pangkep Geopark case study provides lessons for other geoparks and protected areas seeking to foster sustainable tourism development through collaborative governance approaches. This study contributes to the growing knowledge on collaborative governance in sustainable tourism development, particularly in geoparks. It provides a comprehensive analysis of the deliberation and implementation stages, identifying key strategies and best practices. The findings have practical implications for geopark managers, policymakers, and stakeholders seeking to optimize collaborative governance approaches. Furthermore, the study advances the theoretical understanding of collaborative governance by integrating insights from sustainable tourism, protected area management, and stakeholder engagement literature